Saliva analysis in children with active caries before and after dental treatment - Ebru Akleyin; Cansu Osmanoğulları Sarıyıldız; İzzet Yavuz; İsmet Rezani Toptancı (Dental Journal, 2022)
Background: The amount and quality of saliva play important roles in maintaining an intraoral bacterial balance. The quality of saliva is defined by its buffering capacity, viscosity, pH and protein content. The amount of saliva is usually related to the flow rate. Purpose: This study aimed to compare the flow rate, pH, viscosity and buffering capacity of saliva as well as plaque formation in children before and after dental treatment. Methods: Saliva samples were taken from paediatric patients before their treatments and one month after their dental treatments had ended, and these saliva samples were then analysed. For each sample analysis, the GC Saliva-Check Buffer kit (GC Corporation, Tokyo, Japan) was used to evaluate buffering capacity, pH and flow rate, and the GC Saliva-Check Mutans kit (GC Corporation, Tokyo, Japan) was used for the determination of Streptococcus Mutans. GC Tri Plaque ID gel (GC Corporation, Tokyo, Japan) was applied to evaluate plaque maturation. Results: The pre-treatment buffering capacity, pH and viscosity sample values were found to be significantly lower than the post-treatment values (p<0.05). No statistically significant difference was determined in the amount of saliva pre- and post-treatment (p>0.05). When examining plaque maturation, it was determined that all of the post-treatment plaque was pink. Conclusion: This study showed that the pH, viscosity and buffering capacity of saliva had increased significantly post-treatment and that the formation of plaque had decreased in children with active caries after all their dental treatments had been completed.